Analisis Pendapatan dan Kelayakan Usahatani Kunyit di Desa Botolempangan Kecamatan Sinjai Barat: Analysis of Income and Feasibility of Turmeric Farming in Botolempangan Village, West Sinjai District - Nurhayati, Andi Armanto; Megawati, Megawati; Nurdin, Fadilah (Jurnal Ilmiah Manajemen Agribisnis, 2025)
This study aims to determine the factors influencing turmeric farming, as well as the income and feasibility level of turmeric farming in Botolempangan Village, West Sinjai District, Sinjai Regency. The research employed a descriptive quantitative approach with a puRp.osive sampling method involving 45 turmeric farmers as respondents. Data were analyzed using SPSS to examine the factors affecting farm income, namely X1 (land area), X2 (labor), X3 (production cost), X4 (capital), X5 (selling price), and Y (income). Furthermore, production cost, revenue, income, and feasibility analysis using the R/C ratio were calculated. The results showed that land area, capital, and selling price significantly affected turmeric farmers’ income, with an average revenue of IDR 3,512,222 per planting season and an average production cost of IDR 347,505. Thus, the average income obtained by farmers was IDR 3,164,171 per planting season. The feasibility analysis revealed an R/C ratio of 10.84, indicating that turmeric farming in Botolempangan Village is feasible to cultivate since the R/C ratio > 1.